غياب التامور الخلقي - عبد اللطيف, مضر (Latakia University Journal -Medical Sciences Series, 2019)
Congenital absence of the pericardium (CAP) is one of the rarest cardiac congenital anomalies. It can occur as a complete absence of the entire pericardium, absence of the right or left portion of the pericardium or a partial, foramen-like defect of the right or left pericardium. While the majority of cases are clinically silent, multiple reports associate CAP with symptomatic presentation. The most feared complication of CAP is sudden death due to cardiac strangulation across a partial defect of the left pericardium. Given its rare occurrence, most clinicians and imaging specialists will have little experience with this condition and may fail to recognize it on thoracic or cardiac studies. The purpose of this article is to represent a case of complete absence of the left pericardium discovered incidentally during CABG surgery. غياب التامور الخلقي واحد من أندر الشذوذات القلبية الخلقية . يمكن أن يصادف بصورة غياب تام لكل التامور، غياب الجزء الأيسر أو الأيمن من التامور ، أو غياب جزئي للتامور بشكل عيب يشبه الفتحة في التامور الأيمن أو الأيسر . وفي حين تكون معظم الحالات صامتة سريريا الا أن تقارير متعددة تبين وجود تظاهرات عرضية لغياب التامور الخلقي. يمثل الموت المفاجئ بسبب اختناق القلب عبر عيب جزئي في التامور الأيسر المضاعفة الأخطر. و نظرا لندرة مصادفة هذا الشذوذ فان المختصين بوسائل التصوير ذوو خبرة محدودة في هذه الحالة و قد يفشل هؤلاء في كشف الشذوذ بالوسائل التشخيصية الصدرية أو القلبية. الغاية من هذه المقالة عرض حالة سريرية لغياب تامور تام أيسر اكتشف بالمصادفة أثناء جراحة مجازات اكليلية